Organic and inorganic nitrogen amendments reduce biodegradation of biodegradable plastic mulch films - S. Bandopadhyay; S. Bandopadhyay; M. English; M. B. Anunciado; M. Starrett; J. Hu; J. E. Liquet y González; D. G. Hayes; S. M. Schaeffer; J. M. DeBruyn (SOIL, 2023)
Biodegradable mulch films (BDMs) are a sustainable and promising alternative to non-biodegradable polyethylene mulches used in crop production systems. Nitrogen amendments in the form of fertilizers are used by growers to enhance soil and plant-available nutrients; however, there is limited research on how these additions impact the biodegradation of BDMs tilled into soils. A 4-month laboratory incubation study using soil microcosms was used to investigate the effects of inorganic (ammonium nitrate) and organic (urea and amino acids) nitrogen application on biodegradation of BDMs. We investigated the response of soil bacterial, fungal, and ammonia-oxidizing microbial abundance along with soil nitrogen pools and enzyme activities. Microcosms were comprised of soils from two diverse climates (Knoxville, TN, USA, and Mount Vernon, WA, USA) and BioAgri, a biodegradable mulch film made of Mater-Bi®, a bioplastic raw material containing starch and poly(butylene adipate-co-terephthalate) (PBAT). Both organic and inorganic nitrogen amendments inhibited mulch biodegradation, soil bacterial abundances, and enzyme activities. The greatest inhibition of mulch biodegradation in TN soils was observed with urea amendment where biodegradation was reduced by about 6 % compared to the no-nitrogen control. In WA soils, all nitrogen amendments suppressed biodegradation by about 1 % compared to the no-nitrogen control. Ammonia monooxygenase amoA gene abundances were increased in TN soils in all treatments but reduced for all treatments in WA soils. However, a significantly higher nitrate concentration and a lower ammonium concentration were seen for all nitrogen treatments compared to no-nitrogen controls in both TN and WA. This study suggests that the addition of nitrogen, particularly inorganic amendments, could slow down mulch biodegradation but that mulch biodegradation does not negatively affect soil nitrification activity.